2016
DOI: 10.1126/scitranslmed.aac5954
|View full text |Cite
|
Sign up to set email alerts
|

Individualizing liver transplant immunosuppression using a phenotypic personalized medicine platform

Abstract: Posttransplant immunosuppressive drugs such as tacrolimus have narrow therapeutic ranges. Inter-and intraindividual variability in dosing requirements conventionally use physician-guided titrated drug administration, which results in frequent deviations from the target trough ranges, particularly during the critical postoperative phase. There is a clear need for personalized management of posttransplant regimens to prevent adverse events and allow the patient to be discharged sooner. We have developed the para… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
124
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
8

Relationship

6
2

Authors

Journals

citations
Cited by 122 publications
(124 citation statements)
references
References 36 publications
0
124
0
Order By: Relevance
“…In addition, participants were sensitive to these training intensity manipulations, with performance during higher-intensity blocks generally poorer compared to lower-intensity blocks. [43] Importantly, training intensity is also not expected to have a monotonic effect on training improvements. The profiles from individual subjects further demonstrate CU-RATE.AI's potential for optimizing behavioral performance and its rate of improvement.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, participants were sensitive to these training intensity manipulations, with performance during higher-intensity blocks generally poorer compared to lower-intensity blocks. [43] Importantly, training intensity is also not expected to have a monotonic effect on training improvements. The profiles from individual subjects further demonstrate CU-RATE.AI's potential for optimizing behavioral performance and its rate of improvement.…”
Section: Discussionmentioning
confidence: 99%
“…If the subject's response to inputs is dynamic, CURATE.AI can constantly re-calibrate the treatment inputs as the subject's response evolves during the course of treatment, resulting in robust and sustainable interventional optimization. [43] Digital therapeutics has emerged as a non-pharmacological alternative for prevention and treatment of cognitive decline and mild dementia, among others. [32][33][34][35][36][37][38][39][40][41][42] Of note, population-based big data sets are not required or utilized for CURATE.AI implementation.…”
Section: Introductionmentioning
confidence: 99%
“…A recent clinical study demonstrated that drug synergy and antagonism are dose dependent. 85 This is a major issue that should be considered when designing drug combinations. Drug synergy at the in vitro and preclinical levels may not translate into the clinic.…”
Section: Future Perspectivesmentioning
confidence: 99%
“…35 In solid organ transplant immunosuppression, patients are assigned a target range for the blood trough level of tacrolimus. This represents the current standard for assessing the efficacy of immunosuppression.…”
Section: Acs Nanomentioning
confidence: 99%